2019
DOI: 10.3390/su11195408
|View full text |Cite
|
Sign up to set email alerts
|

How Green Human Resource Management Can Promote Green Employee Behavior in China: A Technology Acceptance Model Perspective

Abstract: Green human resource management (GHRM) in the environmental management of organizations has gradually become a key issue in academic circles, and its impact on employees’ green behavior has received increasing attention. However, few studies have explored its impact from the perspective of information delivery. Based on an analysis of the literature, this research discusses the influence route of five types of GHRM practices (employee life cycle, rewards, education and training, employee empowerment, and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(156 citation statements)
references
References 49 publications
6
97
0
2
Order By: Relevance
“…To encourage EGB in the organizations, there have been attempts to find ways by which this green behavior can be influenced (Ardente et al, 2006). A study of EGB among employees in China examined whether EGB can be predicted by green human resource management (green HRM) through the information need of employees (Zhang et al, 2019). Another study among hotel employees in Pakistan showed that EGB was affected by CSR, environmental awareness, environmental concern, and environmental knowledge through the sense of well-being (Ahmed et al, 2020).…”
Section: Need For the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…To encourage EGB in the organizations, there have been attempts to find ways by which this green behavior can be influenced (Ardente et al, 2006). A study of EGB among employees in China examined whether EGB can be predicted by green human resource management (green HRM) through the information need of employees (Zhang et al, 2019). Another study among hotel employees in Pakistan showed that EGB was affected by CSR, environmental awareness, environmental concern, and environmental knowledge through the sense of well-being (Ahmed et al, 2020).…”
Section: Need For the Studymentioning
confidence: 99%
“…Green HRM is defined as the facets of green management that encourage employees' environmentally friendly behavior in the organizations (Renwick et al, 2013). Green HRM is the main platform in organizations through which their environmental performance may be achieved (Zhang et al, 2019). There is evidence that green HRM is linked with EGB; however, it is stated that the literature on green HRM and EGB requires more evidence regarding the underlying mechanisms through which the green HRM affects the EGB (Dumont et al, 2016;.…”
Section: Need For the Studymentioning
confidence: 99%
“…Based on previous empirical studies on voluntary green behavior, this study included five control variables. First, demographic variables would influence individual green behavior [8,12,67]. Hence, the present study controlled for employee gender (1 = female; 2 = male), age (in years), education (1 = junior college or below; 2 = bachelor; 3 = postgraduate), and organizational tenure (in years).…”
Section: Control Variablesmentioning
confidence: 99%
“…In fact, there is accumulating evidence suggesting that the improvement of an organization's environmental performance relies a lot on individual employee behaviors [6][7][8][9]. Therefore, in recent years, organizational scholars have shown great interest in investigating employee green behaviors in the workplace [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation